Development of gel for Aedes aegypti repellent with combination of cinnamon oil (Cinnamomum burmannii Blume) and fennel oil (Foeniculum vulgare Mill) - Sohipah, Evah; Purba, Anny Victor; Djamil, Ratna (Scripta Medica, 2020)
Background/Aim: Aim of this study was to develop efficient mosquito repellent by combining fennel oil (Foeniculum vulgare Mill) and cinnamon oil (Cinnamomum burmannii Blume) in a gel preparation form. Methods: Effectiveness of each oil and its combination as viral repellents was tested by the World Health Organization’s Pesticide Evaluation Scheme (WHOPES) method. Repellent was prepared in gel form. Evaluation of gel preparation included organoleptic properties, homogeneity, pH, viscosity, flow properties, acute skin irritation test and effectiveness test as mosquito repellent. Results: The mosquito protection test for cinnamon oil showed that cinnamon oil was most effective at concentration of 15 % (96.85 %), and fennel oil at 24 % concentration (79.26 %). Within 6 hours, gel made of 24 % fennel oil and 15 % cinnamon oil combination gave protection against 53.49 % mosquitoes. Conclusion: The combination of cinnamon oil and fennel oil can be formulated into gel form with satisfying physical and chemical characteristics and effectiveness against Aedes aegypti mosquitoes for 6 hours.